Spatial and temporal disequilibrium of nuclear distribution in heterothallic Morchella importuna - Peixin He (Elsevier, 2021)
Our previous study found that isolates from morel stipes showed a large proportion of mating type deletion, which implied the nuclear evolution and spatial heterogeneity. In this paper, the specific mating type genes of Mat1-1-1 and Mat1-2-1 in Morchella importuna were analyzed using the relative quantitative method of qRT-PCR to study the uneven nuclear distribution in morel life cycle. The results demonstrated obvious unbalanced distribution of two karyotypes in tested commercially cultivated strains and stipe issue isolates from cultivated ascocarps. The ratio of two mating type genes in tissue isolates from different parts of the ascocarps (base soil, inside and surface of stipe, inside and outside of cap pit) was also different. The disequilibrium also existed in primordium, young ascocarp and mature ascocarp. Moreover, the imbalance in different positions of mature ascocarp (base of stipe, middle of stipe, junction of stipe and cap, middle of cap, and top of cap) gradually converged from bottom to top with the largest difference in base of stipe and almost equal distribution of two mating types in morel caps, which indicated that the deviation of two kinds of nuclei in sexual reproduction stage slowed down. More than half of the protoplast regenerated strains from the heterokaryotic M04 strain were homokaryotic, with the dominant Mat1-1-1 genotype accounted for 85.7%. Overall, the Mat1-1-1 genotype nucleus dominated in all samples from different stage of the life cycle. The imbalance of nuclear distribution during the life cycle of M. importuna may imply the evolutionary-driven nuclear-level selection. This is the first study of spatial and temporal disequilibrium of nuclear distribution in macro-ascomycetes. For scale cultivation, it is necessary to perform genotype integrity testing in potential cultivated strains to ensure the existence of both mating type genes.